2020
DOI: 10.3389/fgene.2020.542017
|View full text |Cite
|
Sign up to set email alerts
|

Transit From Autotrophism to Heterotrophism: Sequence Variation and Evolution of Chloroplast Genomes in Orobanchaceae Species

Abstract: The family Orobanchaceae including autotrophic, hemiparasitic, and holoparasitic species, is becoming a key taxa to study the evolution of chloroplast genomes in different lifestyles. But the early evolutionary trajectory in the transit from autotrophism to hemiparasitism still maintains unclear for the inadequate sampling. In this study, we compared 50 complete chloroplast genomes in Orobanchaceae, containing four newly sequenced plastomes from hemiparasitic Pedicularis , to elucidate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 75 publications
(131 reference statements)
2
10
0
Order By: Relevance
“…This evolutionary pattern indicated that the degradation of the NDH genes in Pedicularis was a gradual process from functional to non-functional. Moreover, gene loss and pseudogenization of NDH genes likely occurred independently across the 13 major clades in Pedicularis ( Zhang et al. 2020 ), which is similar to the pattern of evolution proposed for vegetative and corolla characters ( Ree 2005 , Yu et al.…”
Section: Discussionsupporting
confidence: 64%
“…This evolutionary pattern indicated that the degradation of the NDH genes in Pedicularis was a gradual process from functional to non-functional. Moreover, gene loss and pseudogenization of NDH genes likely occurred independently across the 13 major clades in Pedicularis ( Zhang et al. 2020 ), which is similar to the pattern of evolution proposed for vegetative and corolla characters ( Ree 2005 , Yu et al.…”
Section: Discussionsupporting
confidence: 64%
“…The effective number of codons (ENc) evaluates codon use bias at the genomic level; the lower the ENc value is, the more significant the codon use preference is ( Wright, 1990 ; Zhang et al, 2020 ). …”
Section: Methodsmentioning
confidence: 99%
“…Before calculation, gaps and stop codons between the compared sequences were removed. As the YN model considers sequence evolution characteristics (e.g., transition/transversion ratio and codon usage frequency), it has been used increasingly in molecular evolution research ( Yang and Nielsen, 2000 ; Zeng et al, 2017 ; Zhang R. T. et al, 2020 ). Thus, the YN algorithm was chosen in KaKs_calculator ( Zhang et al, 2006 ) to illustrate the Ka/Ks value and perform selective pressure analysis.…”
Section: Methodsmentioning
confidence: 99%